2021
DOI: 10.1039/d0ay01732a
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate detection via an invertebrate biosensor

Abstract: Improvised explosive devices (IEDs) are constructed from easily obtainable ingredients that are often unregulated and difficult to trace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In a similar vein of using animals to detect explosives, Alsaleh, S., Barron, L., and Sturzenbaum, S. published a paper on the use of the invertebrate nematode Caenorhabditis elegans (worm) for the detection of ground soil perchlorate [ 620 ].…”
Section: General Detectionmentioning
confidence: 99%
“…In a similar vein of using animals to detect explosives, Alsaleh, S., Barron, L., and Sturzenbaum, S. published a paper on the use of the invertebrate nematode Caenorhabditis elegans (worm) for the detection of ground soil perchlorate [ 620 ].…”
Section: General Detectionmentioning
confidence: 99%
“…Engineered C. elegans strains have been used as biosensors to detect a variety of toxic elements in soil and water. For example, fluorescent transgenic lines were able to detect perchlorate, a powerful and toxic oxidizer and soil pollutant (Alsaleh et al, 2021), metal contaminants found in soil pore water, glyphosate (Bailey et al, 2018) and Mn (Bailey et al, 2016; Todt et al, 2016). These examples represent first steps in the application of C. elegans for contaminant assessment in soil.…”
Section: Applications and Future Prospectsmentioning
confidence: 99%
“…[14] More advanced analytical methods for perchlorate residues include ion-selective electrodes equipped with ion carriers within polymer membranes, total reflection X-ray fluorescence [15] and organism-based biosensors. [16] Overall, several methods are not target-specific or poorly quantifiable in the presence of other background ions, and some technologies require costly instruments and well-controlled experimental conditions. Hence, there is a need to develop highly selective, accessible methods.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of analytical methods is commonly used for perchlorate detection, including UV/Vis spectroscopy, [7] integrated mass spectrometry, such as ion or liquid chromatography‐MS, [8–10] ion‐exchange chromatography, [11,12] capillary electrophoresis, [13] and selection of staining assays [14] . More advanced analytical methods for perchlorate residues include ion‐selective electrodes equipped with ion carriers within polymer membranes, total reflection X‐ray fluorescence [15] and organism‐based biosensors [16] . Overall, several methods are not target‐specific or poorly quantifiable in the presence of other background ions, and some technologies require costly instruments and well‐controlled experimental conditions.…”
Section: Introductionmentioning
confidence: 99%